Estratégias cooperativas para o mercado brasileiro de gás natural: uma aplicação do método de Shapley - Ribeiro, Rafael Teixeira da Silva (2017)
The Brazilian natural gas market was developed based on periods of significant increase in the offer, which followed investments in midstream infrastructure, as well as policies to stimulate the consumption. Recently, with the discovery of the pre-salt layer and growth of the natural gas production in the Southeast Region, a similar event capable of promoting this fuel utilization is underway. Besides, the vertical monopoly detained by Petrobras started to decentralize, with announcements of divestments of offshore and onshore fields, importation, transportation and distribution assets and participations. Therefore, during this moment of growth in the natural gas offer and market decentralization, it’s possible to identify a new opportunity to enhance the utilization of this fuel in Brazil, which will require the collaboration among existing and new agents. Within this scenario, this paper describes the use of the Cooperative Game Theory and application of Shapley Allocation Method as a way to evaluate the influence of different agents regarding production, transportation and distribution on the Southeast Region, serving as a basis for strategic analysis, public policies development, investment attraction and further actions which can unlock the Brazilian natural gas market. Finally, the results obtained with the model application showed that the transportation infrastructure, due to its relative low cost, does not play a relevant role in the benefits allocation. It’s also possible to observe the relevant influence of offshore natural gas, as well as the local distribution companies, as main mechanisms to increase natural gas consumption in Brazil.